The role of emotions in the control-resistance dyad - Duarte, H.; Palermo, O.; Arriaga, P. (Scandinavian Journal of Management, 2018)
This paper investigates the implications of perceived Socio-Ideological Organizational Controls (SIOC) dimensions on actors’ lived experiences in the workplace. We explored whether emotions mediate the dyad control-resistance. Data was collected from 385 participants, via a self-administered questionnaire framed as part of a cross-sectional survey design. Our findings suggest that SIOC dimension related to the promotion of values is an important predictor of experiencing higher positive emotions and lower negative emotions at work. The positive emotions, in turn, predict higher organisational citizenship levels and lower resistance behaviours. Based on these findings, we discuss the role and effectiveness of organisational controls inspired by discursive practices.